Modelling fatigue induced change in hyperelastic response of SBR/NR blends - Nambiar, Adtihya; Mythravaruni, P. (Frontiers in Mechanical Engineering, 2025)
Traditionally, fatigue of hyperelastic materials has been modelled using Continuum Damage Mechanics. Although CDM can very accurately simulate damage due to fatigue, CDM can simulate only a small control volume of the material efficiently. If the model is not extremely precise, simulating the bulk structure becomes computationally costly and more error-prone. A systematic approach is utilised to examine the fatigue-induced property change in rubber composites. Hyperelasticity, and failure characteristics, such as tensile strength and elongation at break, are used to create the model. In this paper, the Energy Limiter approach is used to develop a constitutive model that can capture the variation of material parameters with fatigue. To model the variation of material parameters with the number of loading cycles, uniaxial tensile tests are conducted after subjecting the samples to different number of fatigue loading cycles. The experimental data obtained from the tensile test is used in an optimisation algorithm to find the model parameters that provide the best fit to the experimental behaviour. With the predicted parameters, the tensile test is simulated in ABAQUS incorporating element deletion and the results of the ABAQUS simulation are compared with experimental behaviour and model response. Finally, a relation for model parameters as a function of life factor is obtained.